Karakteristik Fisik Dan Organoleptik Sediaan Serbuk Flavour Kepala Udang Windu (Penaeus monodon) Pada Perbedaan Suhu Pengeringan - Mismawati, Andi; Diachanty, Seftylia; Rusdin, Ilmiani; Hasanah, Rafitah (Universitas Negeri Gorontalo, 2024)
Shrimp heads will harm the environment if not managed properly. Utilization of this by-product as a flavoring agent by adding fillers widely used, but powdered preparations without added fillers have not been reported. This study aimed to make flavored preparations from tiger prawn heads with different drying temperatures acceptable to consumers. The oven drying method performed at temperatures of 100oC (SH1), 125oC (SH2), and 150oC (SH3) and the resulting fiber was tested for physical characteristics (yield and color test) and organoleptic tests (sensory test and hedonic test). The color test results show changes in the values of brightness (L*) of 49.07-55.28, reddish (a*) of 8.41-10.39, yellowish (b*) of 25.10-32.65, and degrees of whiteness (WI) of 40.23- 46.48 where this value decreases as temperature increases. The sensory test results showed significant divergentbetween the odor treatments but were not significantly different in color and appearance. The hedonic data analysis indicated that the panelists' preference for hueranged between 7-8 (liked-very like), aroma, 6-7 (rather liked), taste, 5-6 (neutral-liked somewhat), and texture, 7-8 (like-really like). Generally, based on physical and organoleptic tests, it showed specific characteristics of shrimp powder at a drying temperature of 100 oC (SH1).